À la croisée des idées de Francisco Ferrer et Célestin Freinet : l’expérience de l’école Elisée Reclus à Barcelone en 1935-1936 - Cécile Morzadec (Éducation et Socialisation)
The little-known experience of the Elisée Reclus school created in 1935 by the Aragonese anarchist educationalist Félix Carrasquer is interesting in many ways. It gives us an idea of the circulation of new education and anarchist education ideas in the 1930s, as well as an insight into the workings of an unusual school at the crossroads of the educational ideas of Francisco Ferrer (1859-1909) and Célestin Freinet (1896-1966). We will see how Félix Carrasquer brought these two educational models together in the concrete proposals of his school and how he brought his own writings together over time, since between 1935-1936 and 1981-1988, he left us several testimonies that reveal an evolution in his positions. By evoking a project for a “free” or “democratic” school in 1935-1936, which he would later call “educación autogestionada” [“self-managing” education] (Carrasquer, 1981), we can ask ourselves whether he was not a visionary in education: was he simply passing on models, or inspiring a new form of education?